2018
DOI: 10.1038/modpathol.2017.187
|View full text |Cite
|
Sign up to set email alerts
|

Combined mutation and copy-number variation detection by targeted next-generation sequencing in uveal melanoma

Abstract: Uveal melanoma is a highly aggressive cancer of the eye, in which nearly 50% of the patients die from metastasis. It is the most common type of primary eye cancer in adults. Chromosome and mutation status have been shown to correlate with the disease-free survival. Loss of chromosome 3 and inactivating mutations in BAP1, which is located on chromosome 3, are strongly associated with 'high-risk' tumors that metastasize early. Other genes often involved in uveal melanoma are SF3B1 and EIF1AX, which are found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 35 publications
(34 reference statements)
8
49
1
Order By: Relevance
“…EIF1AX mutations were detected in the present study in 19% of UM, which is consistent with that reported by other groups [11,14,18,25]. Interestingly, two UM demonstrated mutations in both EIF1AX and SF3B1 despite previous reports describing that these occur in a mutually exclusive manner [11,25].…”
Section: Eif1ax Mutationssupporting
confidence: 92%
See 2 more Smart Citations
“…EIF1AX mutations were detected in the present study in 19% of UM, which is consistent with that reported by other groups [11,14,18,25]. Interestingly, two UM demonstrated mutations in both EIF1AX and SF3B1 despite previous reports describing that these occur in a mutually exclusive manner [11,25].…”
Section: Eif1ax Mutationssupporting
confidence: 92%
“…The frequency of BAP1 mutations in the present study was 43% in total, occurring in 82% of M3-UM; these data are consistent with the findings of others [11,14,19,25]. The presence of a BAP1 mutation in UM was associated with a worse survival.…”
Section: Bap1 Mutationssupporting
confidence: 92%
See 1 more Smart Citation
“…New targeted essays are developed so that next‐generation sequencing can allow for a simultaneous assessment of selected gene mutations and chromosomal copy number (Smit et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Mutation analysis of GNAQ, GNA11, EIF1AX, SF3B1, and BAP1 was performed with Sanger sequencing and Ion Torrent next-generation sequencing (NGS; Thermo Fisher Scientific, Waltham, MA) as described before. 32 UM without a GNAQ or GNA11 mutation were sequenced for PLCB4 and CYSLTR2. If the tumor did not harbor a mutation in EIF1AX, SF3B1 or BAP1, mutation analysis for SRSF2 was performed.…”
Section: Mutation Detectionmentioning
confidence: 99%